The Dynamics of Human Environmental Behaviour: A Behavioural Approach to Nature Conservation Efforts - Ilal Ilham; Aldri Oktanedi (Talenta Publisher, 2024)
ABSTRACT This article examines the dynamics of human environmental behavior through a behavioral approach to nature conservation efforts. The research highlights the importance of pro-environmental behavior, which can be influenced by social norms, economic incentives, and environmental education. By analyzing various studies and successful interventions applied in several regions, such as the recycling program in Surabaya and the